Churg-Strauss syndrome: outcome and long-term follow-up of 38 patients from a single Italian centre - R. Neri; M. Mosca; A. d'Ascanio; R. Talarico; E. Catarsi; S. Grossi; A. Della Rossa; C. Baldini; A. Tavoni; S. Bombardieri (PAGEPress Publications, 2011)
Objective: This study was aimed at verifying any potential correlation between anti-myeloperoxidase antineutrophil cytoplasmic antibodies (ANCA-MPO) and clinical features and outcome indices in Churg-Strauss Syndrome (CSS). Methods: Thirhty-eight Churg-Strauss syndrome patients were selected from the medical records of all vasculitis patients attending the Rheumatology and Immunology Unit at the Department of Internal Medicine of the University of Pisa in the decades between 1989 and 2008. Data were analysed retrospectively. Statistical analyses of the results were carried out using the Mann-Whitney test to determine the correlations between the clinical and serological parameters. Qualitative variables were compared using contingency table analysis and Fisher's exact test. Results: ANCA-MPO were detected in15/38 (39%) patients. Positive ANCA status was associated with peripheral neuropathy (p=0.0006), whereas negative ANCA status was associated with lung involvement (p=0.002). Relapses were strongly associated with positive ANCA status (p=0.01) and with an increase in- or a reappearence of ANCA-MPO levels (p=0.006). Finally, ANCA-MPO were significantly associated with neurological damage (p=0.003). Conclusions: The presence or absence of ANCA-MPO identify different clinical subsets in CSS. Overall, ANCA-MPO appears as a useful tool in the monitoring of CSS and in particular a good predictor of CSS relapses